Xanthine Oxidase Does Not Contribute to Apoptosis after Brain Hypoxia-Ischemia in Immature Rabbits - Moretti, Anthony (Hindawi Publishing Corporation, 2013)
Background. The mechanisms involving the initiation of apoptosis after brain hypoxia-ischemia through caspase activation are not fully defined. Oxygen free radicals may be an important mediator of caspase initiation with reactive oxygen species generated by xanthine oxidase (XO) being one potential source. The purpose of this study was to examine the role of XO in apoptosis after global cerebral injury. Methods. Immature rabbits were subjected to 8 minutes hypoxia and 8 minutes ischemia and then 4 hours of reperfusion. In one group (n = 5), the XO substrate xanthine was infused to generate more oxygen free radicals to promote apoptosis while in another (n = 5), the XO inhibitor allopurinol was given to reduce apoptosis by preventing free radical production (n = 5). Control animals (n = 4) received the vehicles. Caspase 3, 8, and 9 enzyme activities were measured in the cerebral cortex, hippocampus, cerebellum, thalamus, and caudate. Results. Administration of xanthine increased (P < 0.05) caspase 3 activity but only in the hippocampus, and pretreatment with allopurinol did not reduce it. No differences (P > 0.05) were found in any other region nor were there any changes in caspases 8 or 9 activities. Conclusion. We conclude that XO is not a major factor in inducing apoptosis after hypoxic-ischemic brain injury.